Enhancing Learning Outcomes in Physical Education through Project-Based Learning: A Quasi-Experimental Study on Butterfly Stroke Instruction - Kurnia Rusli; Sujarwo Sujarwo; Jusmawati Jusmawati; Ferawati Ferawati; Agus Ismail (AL-ISHLAH: Jurnal Pendidikan, 2025)
The butterfly stroke is widely regarded as the most technically and physically demanding swimming style, often posing challenges for physical education students due to its complex coordination of arm movements, leg kicks, and breathing techniques. Project-Based Learning (PjBL) has shown promise in enhancing student engagement, collaboration, and reflective learning in physical education settings. This quasi-experimental study aimed to evaluate the effectiveness of PjBL in improving students’ learning outcomes for the butterfly stroke. Two groups participated: an experimental group exposed to PjBL methods and a control group that received traditional instruction. The intervention was conducted over a designated instructional period within a swimming course. Statistical analysis revealed a significant difference in learning outcomes between the two groups. The experimental group achieved a mean gain score 10.83% higher than the control group, with a t(70) = 8.102, p .001. The 95% confidence interval for the mean difference ranged from 8.17% to 13.50%, indicating a consistent and substantial improvement in performance attributed to the PjBL approach. Findings suggest that PjBL fosters improved psychomotor, cognitive, and affective domain development in students learning the butterfly stroke. Enhanced student motivation, teamwork, and reflective engagement appear to be key factors contributing to the learning gains observed. Project-Based Learning significantly enhances learning outcomes in swimming lessons focused on the butterfly stroke. This pedagogical approach can effectively support the development of complex motor skills in physical education.